"Respect the way I need to communicate with you": Healthcare experiences of adults on the autism spectrum. (October 2015) - Nicolaidis, Christina; Raymaker, Dora M; Ashkenazy, Elesia; McDonald, Katherine E; Dern, Sebastian; Baggs, Amelia EV; Kapp, Steven K; Weiner, Michael; Boisclair, W Cody
Our objective was to obtain an in-depth understanding of autistic adults' experiences with healthcare and their recommendations for improving care. Our academic–community partnership used a community-based participatory research approach to conduct semi-structured, open-ended interviews with 39 autistic adults and 16 people who had experience supporting autistic adults in healthcare settings. Participants identified patient-level, autism-related factors that impact healthcare interactions, including verbal communication skills, sensory sensitivities, challenges with body awareness, slow processing speed, atypical non-verbal communication, and challenges with organization. However, the success of healthcare interactions largely depended on the interplay between patient- and provider-level factors, as well as the larger context in which patients were receiving care. Provider-level factors included providers' knowledge about autism in adults, incorrect assumptions about individual patients, willingness to allow written communication, use of accessible language, openness to providing other accommodations, and skill in appropriately incorporating supporters. System-level factors included the availability of supporters, complexity of the healthcare system, accessibility of healthcare facilities, and stigma about autism. Further efforts are needed to empower patients, adequately train providers, increase the accessibility of the healthcare system, and decrease discrimination.